Podejście umiarkowane w sporze o możliwość i użyteczność moralną kodyfikacji norm etycznych - Klimczuk, Andrzej (Annales. Etyka w Życiu Gospodarczym, 2014)
The popularisation of code elaboration addressed to various social groupsis one of the features of the modern world. However, among researchers of thisphenomenon a full consensus on the moral validity and usefulness of this activitydoes not exist. The article closely reviews the literature with regard to the reasonsfor the creation of a moderate position on the codification of ethical standards.The essay brings closer the main concepts of ethical codes and positions for theiradoption and rejection. Attention is paid to ways of increasing the effectivenessof codes and the ethical decision-making procedure in a manner that underminessupporters and opponents of codification approaches.